2015
DOI: 10.1212/wnl.0000000000001990
|View full text |Cite
|
Sign up to set email alerts
|

The 2D:4D ratio, a proxy for prenatal androgen levels, differs in men with and without MS

Abstract: The 2D:4D ratio, a proxy for prenatal androgen levels, differs in men with and without MS ABSTRACT Objective: To determine whether the 2D:4D ratio (ratio of the second and fourth digit lengths), a proxy for lower prenatal androgen to estrogen ratio, differs in men with and without multiple sclerosis (MS) using a case-control study design. Methods:We obtained 2 digital scans of the right hand for men with MS presenting to a scheduled clinic visit at a large MS referral center, and for men without autoimmune or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 35 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…Since most of daily living activities are the main indicators of independence and are associated with manual dexterity, the patient can increase hand grip strengh by appropriate exercise and muscle strengthening movements to improve the quality of life and reduce EDSS level. In this study it was found that the 2D: 4D ratio was not related to the intensity (level) of disease in females suffering MS which is consistent with the research by Bove et al (2015) which was conducted on men suffering MS and found that the 2D: 4D ratio was higher in MS patients than the without MS group and this ratio is not associated with age and testosterone level in adults or clinical characteristics of MS. Disorders of the immune system which is separated into two branches of humoral and Cellular immunity can result in autoimmune diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Since most of daily living activities are the main indicators of independence and are associated with manual dexterity, the patient can increase hand grip strengh by appropriate exercise and muscle strengthening movements to improve the quality of life and reduce EDSS level. In this study it was found that the 2D: 4D ratio was not related to the intensity (level) of disease in females suffering MS which is consistent with the research by Bove et al (2015) which was conducted on men suffering MS and found that the 2D: 4D ratio was higher in MS patients than the without MS group and this ratio is not associated with age and testosterone level in adults or clinical characteristics of MS. Disorders of the immune system which is separated into two branches of humoral and Cellular immunity can result in autoimmune diseases.…”
Section: Discussionsupporting
confidence: 90%
“…25 This sexually dimorphic ratio can be considered as a lifelong signature of prenatal hormonal levels: a higher ratio has been shown to be associated with a lower in utero balance of androgens to estrogen. In a cohort of 120 men with MS, we found a lowered 2D:4D ratio in men with MS compared to controls, reflecting lowered prenatal testosterone levels and supporting a role for lowered testosterone as a risk factor for MS. 26 …”
Section: Ms Risk-testosterone In the Prenatal Periodmentioning
confidence: 99%
“…If MS risk is influenced by developmental exposures, then the prenatal and perinatal periods should play a particularly large role in shaping more proximal myelin development, but also in programming lifelong proinflammatory trajectories and myelin regulation. For example, prenatal hormone levels have been associated with MS risk [ 135 , 136 ] and most convincingly, low prenatal levels of the hormone vitamin D [ 137 ], which may set the stage for development and intergenerational immunologic changes [ 138 , 139 ]. Similarly, maternal adiposity, whose effects on offspring immune trajectories could result from metabolic programming of growth trajectories or the timing of puberty, is also beginning to show an association with MS [ 140 ].…”
Section: Theoretical Framework Initial Findings and Predictionsmentioning
confidence: 99%